Renal cell tumor with sex-cord/gonadoblastoma-like features: analysis of 6 cases - Wang, Gang; Amin, Mahul B; Grossmann, Petr; Ptáková, Nikola; Hayes, Malcolm; Hartmann, Arndt; Agaimy, Abbas; Lopez, Jose I; Michal, Michal; Hes, Ondrej (Virchows Archiv, 2022)
Renal tumors are one of the most diverse groups of tumors in pathology. Many emerging and important entities have been described recently. Here, we describe a series of renal tumors occurring in adult patients, with distinct histologic features, and with a striking resemblance to gonadal sex cord-stromal tumors. Patients were three males and three females aged 39-82 years; tumor size ranged from 0.9 to 3.6 cm. Five tumors were organ-confined, while one case had a focal perinephric invasion. No aggressive behavior was noted. Microscopically, all the tumors were composed of loose or compact tubular structures with elongated or angulated shapes. The tumor cells were cylindrical or cuboidal, with pale eosinophilic cytoplasm, irregular nuclear membranes, and ISUP/WHO grade 2-3 nuclei. The stroma showed focal or prominent collagen deposition with prominent basement membrane-like material. In all cases, the tumor cells were positive for PAX8, CD10, and vimentin and retained positivity for FH and SDHB. Cathepsin K and AMACR were variably positive. Tumors were negative for HMB45, Melan A, TFE3, SF1, inhibin, calretinin, ER, PR, CD117, OCT3/4, SALL4, ALK, and WT1. Molecular studies showed no abnormalities in TFEB, TFE3, or FH genes. In 3/4 tested cases, mutation of the NF2 gene was present. In all the tested male cases, loss of the Y chromosome was found. In the relatively short follow-up, these tumors appear to have indolent behavior. This study expands the clinicopathologic diversity of renal cell tumors by describing a series of potentially novel tumors morphologically resembling gonadal sex-stromal tumors, with negativity for sex cord-stromal markers. Potential relationship to recently described biphasic hyalinizing psammomatous renal cell carcinoma is discussed.
Keywords: senioři; Carcinoma, Renal Cell; senioři nad 80 let; lidé; imunohistochemie; Middle Aged; mužské pohlaví; karcinom z renálních buněk; Gonadoblastoma-like; nádory vaječníků; Adult; Renal cell carcinoma; Sex cord-stromal tumor-like; NF2 mutation; Gonadoblastoma; Kidney Neoplasms; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Biomarkers, Tumor; Biphasic hyalinizing psammomatous renal cell carcinoma; Aged, 80 and over; Immunohistochemistry; ženské pohlaví; nádorové biomarkery; Humans; transkripční faktory BHLH-Zip; lidé středního věku; dospělí; Kidney; Female; Aged; Ovarian Neoplasms; nádory ledvin; Male; gonadoblastom